2015
DOI: 10.1136/gutjnl-2015-310022
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of α4β7 and GPR15 on homing of effector and regulatory T cells from patients with UC to the inflamed gut in vivo

Abstract: ObjectiveGut homing of lymphocytes via adhesion molecules has recently emerged as new target for therapy in IBDs. We aimed to analyse the in vivo homing of effector (Teff) and regulatory (Treg) T cells to the inflamed gut via α4β7 and G protein receptor GPR15.DesignWe assessed the expression of homing receptors on T cells in peripheral blood and inflamed mucosa. We studied the migration pattern and homing of Teff and Treg cells to the inflamed gut using intravital confocal microscopy and FACS in a humanised mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 53 publications
6
106
3
1
Order By: Relevance
“…This raises the question of whether GPR15 is not involved in the migration of Tregs into the inflamed colon, a concept favored by Fischer and colleagues. They showed in a humanized mouse model that α4β7 integrin is important for homing of UC Tregs into the colon (18). Interestingly, we detected only a very small population of Tregs that coexpress α4β7 and GRP15 in PBMCs of healthy individuals and UC patients, providing evidence that there might be differences in function and migration among α4β7 + Tregs, GRP15 + Tregs, and α4β7 + GRP15 + Tregs.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This raises the question of whether GPR15 is not involved in the migration of Tregs into the inflamed colon, a concept favored by Fischer and colleagues. They showed in a humanized mouse model that α4β7 integrin is important for homing of UC Tregs into the colon (18). Interestingly, we detected only a very small population of Tregs that coexpress α4β7 and GRP15 in PBMCs of healthy individuals and UC patients, providing evidence that there might be differences in function and migration among α4β7 + Tregs, GRP15 + Tregs, and α4β7 + GRP15 + Tregs.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, they imply that the expression of GPR15 might be downregulated after binding to the potential ligand or within the inflamed environment or that GPR15 is not an exclusive master regulator for the migration of Tregs into the inflamed colon. A former study in a humanized mouse model by Fischer and colleagues (18) suggested that α4β7 integrin is crucial for homing of Tregs from UC patients into the colon. Well in line with their results, we detected an increased expression of α4β7 integrin on Tregs from peripheral blood mononuclear cells (PBMCs) of UC patients ( Figure 5A), similar to our results obtained for GPR15 expression ( Figure 2B).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These infections were prob ably related to natalizumab induced blockade of T cell homing to the brain via α4β1 integrins, suggesting that a more specific blockade of α4β7 integrins was important. Subsequently, the α4β7 integrin specific antibody vedolizumab was developed and showed efficacy in clinical phase III trials for remission induction and maintenance in Crohn's disease and ulcerative colitis [58][59][60][61][62][63] .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Intravital confocal microscopy analyses upon adoptive transfer of T cells were performed according to a previously published study (53 RPMI 1640 medium (10% FCS, 1% penicillin-streptomycin, 1% nonessential amino acids, 1% L-glutamine, and 0.1 % β-mercaptoethanol) and activated with 10 μg/ml plate-bound anti-CD3 (clone 145-2C11; BioXcell) and 1 μg/ml soluble anti-CD28 (clone 37.51; BioXcell) antibodies. T cell cultures were additionally supplemented with 10 μg/ml soluble anti-IFN-γ (clone XMG1.2; BioXcell) antibody, either alone or together with 2 ng/ml recombinant IL-7 (rIL-7) (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%